Uranium(VI)/Plutonium(IV) Separation from Spent MOX Fuels Using a Single Monoamide Extractant: The PUMAS Process - Michaud Solenne; Duterme Amandine; Costenoble Sylvain; Lengrand Fabien; Vanel Vincent; Moeyaert Pauline; Sarrat Pierre; Sorel Christian; Miguirditchian Manuel (EPJ Web of Conferences)
In the context of the development of generation IV reactors, solvent extraction process is under development for the reprocessing of spent nuclear fuels. A monoamide extractant was found to be a suitable replacement for TBP. This extractant allows plutonium(IV) back-extraction by changing the acidity instead of the plutonium oxidation state. This paper sum up the methodology and the different hot tests performed in Atalante facility to demonstrate uranium(VI)/plutonium(IV) separation from used MOX fuels using this single monoamide extractant with the so-called PUMAS process.